Effects of Micropit Depths on Tribology Performance of Textured Port Plate Pair. (11th November 2018) - Deng, Haishun; He, Shiju; Mao, Feiyu; Wang, Chuanli
Abstract : In order to improve the friction and wear performance of textured port plate pair, effects of the micropit depth on the tribology performance is studied in the paper. The relation between the micropit depth and the port plate pair's oil loading carrying capacity is analyzed in theory; with the friction coefficient, the wear volume and the surface roughness as the evaluation criteria, effects of the micropits' depth on the tribology performance are investigated. The conclusions are shown as follows: oil loading capacity would come to its peak when the oil film thickness is equal to the micropit depth; the optimal micropit depth is unrelated to the area ratios and micropits' diameters. With the same parameters, the effects of antifriction is optimal when the micropits' depth is 10 μ m, while antiwear and surface integrity are optimal when 15 μ m. When the micropits' depth is 5 μ m, the antiwear, surface roughness, and antifriction are worse compared with those of the untextured port plate pair.